Jn 8,25 au risque de l'herméneutique: Les versions anciennes - Rico, Christophe (Revue biblique, 2023)
In the following pages we shall examine the Syriac, Coptic and Latin versions of Jn 8:25. A special attention will be paid to the Vulgate translation, which in this particular verse has often been criticized. In order to fully appreciate its soundness, one has to understand the interpretative rules which Saint Jerome used to apply in his translation.